2015
DOI: 10.1177/1524839915587265
|View full text |Cite
|
Sign up to set email alerts
|

Against Colorectal Cancer in Our Neighborhoods, a Community-Based Colorectal Cancer Screening Program Targeting Low-Income Hispanics

Abstract: The detailed description of the development processes and costs of this health promotion program targeting low-income Hispanics will inform health program decision makers about the resource requirements for planning and developing new programs to reduce disease burden in communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…A total of 40 studies 1421,2427,29,3133,3538,4042,45,46,48,50,52,5465 were conducted in the U.S., and 13 studies 22,23,28,30,34,39,43,44,47,49,51,53,66 were conducted in other high-income countries. 13 The U.S. studies were distributed in the following geographic regions: Northeast, 15,18,24,37,38,46,50,52,58,62,63 Southeast, 17,18,26,27,55,64,65 Midwest, 14,16,25,36,42,45,54 Southwest, 19,20,29,33,35,56,5961 and West. 21,29–32,40,41,48,57 There were non-U.S. studies from Japan 22 and Spain 23 for breast cancer; from Japan 28 and Canada 30 for cervical cancer; and from Netherlands, 34,39 France, 47,49,53 Hong Kong, 51 South Korea, 66 and Italy 43,44 for colorectal cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 40 studies 1421,2427,29,3133,3538,4042,45,46,48,50,52,5465 were conducted in the U.S., and 13 studies 22,23,28,30,34,39,43,44,47,49,51,53,66 were conducted in other high-income countries. 13 The U.S. studies were distributed in the following geographic regions: Northeast, 15,18,24,37,38,46,50,52,58,62,63 Southeast, 17,18,26,27,55,64,65 Midwest, 14,16,25,36,42,45,54 Southwest, 19,20,29,33,35,56,5961 and West. 21,29–32,40,41,48,57 There were non-U.S. studies from Japan 22 and Spain 23 for breast cancer; from Japan 28 and Canada 30 for cervical cancer; and from Netherlands, 34,39 France, 47,49,53 Hong Kong, 51 South Korea, 66 and Italy 43,44 for colorectal cancer.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…1417,2022,24,25,29–32,3443,4550,5254,5658,62,64,66 Most included cost-effectiveness analyses, reporting ICERs, 1416,18,2024,26,27,2933,3538,40,41,45,47,49,57,60,62,6466 whereas some reported only cost estimates. 17,19,25,28,34,39,4244,46,48,5456,58,59,61 Only one study reported cost–benefit estimates. 63 Of the studies reporting cost-effectiveness estimates, the majority had comparators that did not receive an intervention (usual-care group).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…fecal occult blood testing, such as the FIT, which is available as an inexpensive and easy to use home kit. It is estimated that CRC screening could prevent about a third of the annual deaths; yet screening rates remain low, especially among the uninsured and underinsured populations (Shokar et al 2015). Furthermore, the CRC mortality rate declined in the past two decades as a result of screening, but it was in primarily white populations, and racial disparities persist (Green and Coronado 2014).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…A different set of studies focused on the development of practical models for colorectal cancer screening and patient navigation for populations known to be at higher risk for CRC mortality or CRC late stage diagnosis (Bolen, Adams, and Shenson 2007;Escoffery et al 2015;Shokar et al 2015;Beyer et al 2016;Brenner et al 2016).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation